Transition-Metal-Catalyzed Enantioselective Heteroatom–Hydrogen Bond Insertion Reactions - Zhu, Shou-Fei; Zhou, Qi-Lin (Accounts of chemical research, 2012)
Carbon–heteroatom bonds (C–X) are ubiquitous and are among the most reactive components of organic compounds. Therefore investigations of the construction of C–X bonds are fundamental and vibrant fields in organic chemistry. Transition-metal-catalyzed heteroatom–hydrogen bond (X–H) insertions via a metal carbene or carbenoid intermediate represent one of the most efficient approaches to form C–X bonds. Because of the availability of substrates, neutral and mild reaction conditions, and high reactivity of these transformations, researchers have widely applied transition-metal-catalyzed X–H insertions in organic synthesis. Researchers have developed a variety of rhodium-catalyzed asymmetric C–H insertion reactions with high to excellent enantioselectivities for a wide range of substrates. However, at the time that we launched our research, very few highly enantioselective X–H insertions had been documented primarily because of a lack of efficient chiral catalysts and indistinct insertion mechanisms. In this Account, we describe our recent studies of copper- and iron-catalyzed asymmetric X–H insertion reactions by using chiral spiro-bisoxazoline and diimine ligands. The copper complexes of chiral spiro-bisoxazoline ligands proved to be highly enantioselective catalysts for N–H insertions of α-diazoesters into anilines, O–H insertions of α-diazoesters into phenols and water, O–H insertions of α-diazophosphonates into alcohols, and S–H insertions of α-diazoesters into mercaptans. The iron complexes of chiral spiro-bisoxazoline ligands afforded the O–H insertion of α-diazoesters into alcohols and water with unprecedented enantioselectivities. The copper complexes of chiral spiro-diimine ligands exhibited excellent reactivity and enantioselectivity in the Si–H insertion of α-diazoacetates into a wide range of silanes. These transition-metal-catalyzed X–H insertions have many potential applications in organic synthesis because the insertion products, including chiral α-aminoesters, α-hydroxyesters, α-hydroxyphosphonates, α-mercaptoesters, and α-silyl esters, are important building blocks for the synthesis of biologically active compounds. The electronic properties of α-diazoesters and anilines markedly affected the enantioselectivity of N–H insertion reaction, which supports a stepwise ylide insertion mechanism. A novel binuclear spiro copper complex was isolated and fully characterized using X-ray diffraction analysis and ESI-MS analysis. The positive nonlinear effect indicated that binuclear copper complexes were the catalytically active species. The 14-electron copper centers, trans coordination model, perfect C 2-symmetric chiral pocket, and Cu–Cu interaction facilitate the performance of the chiral spiro catalysts in X–H insertion reactions.